The Ultrastructure, Spatial Distribution, and Osmium Tetroxide Binding of Lipofuscin and Melanosomes in Aging Monkey Retinal Epithelium. (3rd August 2018) - Gouras, Peter; Brown, Kristy R.; Mattison, Julie A.; Neuringer, Martha; Nagasaki, Takayuki; Ivert, Lena
ABSTRACT: Purpose : To examine the ultrastructure of lipofuscin bodies and melanosomes in retinal epithelium of elderly rhesus monkeys and determines changes in their number and morphology as a function of retinal eccentricity. Methods : Electron microscopy was used to describe and quantify two major organelles in elderly monkey retinal epithelium, lipofuscin bodies and melanosomes, at different retinal loci extending from the macula to the peri-macula, equator, periphery and ora serrata. Osmium tetroxide was used to distinguish lipofuscin bodies from melanosomes. Results: Lipofuscin bodies and melanosomes diminished in number with advanced age but there was an inverse relationship between these two organelles. Lipofuscin bodies were more numerous in the macula and melanosomes more numerous in the peripheral retina. Three types of lipofuscin bodies were identified: 1) smaller and tending to locate in the middle third of the epithelial cell, 2) larger, less common, and located more basally, and 3) extremely rare, melano-lipofuscin, containing a melanosome. When osmicated, all lipofuscin bodies contained electron dense materials. When osmium tetroxide was not used for fixation, the first two types of lipofuscin bodies lost their electron densities while the third type retained its electron density due to the melanosome it contained. Conclusion : As previously reported for human retina, lipofuscin is most abundant in the macular and peri-macular epithelium and least abundant in the periphery, whereas melanosomes show the opposite relationship.This distribution pattern could contribute to the macula's greater vulnerability to photo-toxicity . Three types of lipofuscin bodies are found in aging monkey retinal epithelium. All types contain electron dense material, but the most prominent two types lose their densities in the absence of osmium tetroxideduring fixation. Most of the electron densities in lipofuscin bodies must contain a material that binds strongly to osmium tetroxide such as polyunsaturated fatty acids.